Associations of nicotine dependence and fat distribution in Chinese male adults: a cross-sectional study in Lanxi, China. Issue 3 (12th March 2019) - Wei, Chen; Ye, Sunyue; Sheng, Jessica Ruolin; Ma, Xiaoguang; Ru, Yuan; Zhang, Liang; Guo, Huilan; Zhu, Shankuan
Abstract : Introduction: Previous studies have showed association between smoking and central fat distribution. However, the impact of smoking on whole body fat distribution, particularly peripheral fat distribution remains unclear. Methods: Nicotine dependence was assessed in a total of 1264 male adults aged 18–80 years using the Fagerström Test for Nicotine Dependence (FTND). Smoking status was categorised as non-smokers, former and current smokers with very low, low/moderate, or high FTND scores. Body fat distribution was determined using the dual energy X-ray absorptiometry and anthropometric measurements. Multivariable linear regression models were applied to examine the adjusted associations between body fat distribution and smoking in all participants, and its association with FTND scores in the current smokers. Results: Greater waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), trunk fat percentage (%TF), android fat percentage (%AF) and android-to-gynoid fat mass ratio (AOI); but lower legs fat percentage (%LegF), limb fat percentage (%LimbF) and gynoid fat percentage (%GF) were found in current smokers with high FTND scores compared with non-smokers. In current smokers aged 60 years or older, FTND scores had positive associations with WC, WHR, WHtR, %TF, %AF and AOI, and negative associations with %LegF, %LimbF and %GF. Conclusions: Nicotine dependence was positively associated with central fat distribution and negatively associated with peripheral fat distribution in Chinese male adults, particularly in those older or heavy smokers, and these associations were independent from body mass index, which might be due to long exposure to smoking.